MiR-410 induces stemness by inhibiting Gsk3β but upregulating β-catenin in non-small cells lung cancer - Ke, Xixian (Oncotarget, 2017)
Our previous research indicated miR-410 played a critical role in promoting the tumorigenesis and development of NSCLC (non-small cells lung cancer). MiR-410 has been recently reported to be crucial for development and differentiation of embryonic stem cells. But it remains elusive whether miR-410 stimulates the stemness of cancer until now. Herein, we identify miR-410 induces the stemness and is associated with the progression of NSCLC. We demonstrate miR-410 increases the levels of stem cells marker Sox2, Oct4, Nanog, CXCR4 as well as lung cancer stem cells surface marker CD44 and CD166. MiR-410 promotes stem cells-like properties such as proliferation, sphere formation, metastasis and chemoresistance. Moreover, Gsk3β is directly targeted and post-transcriptionally downregulated by miR-410. Also, the expression levels of miR-410 and Gsk3β may be correlated to clinicopathological differentiation in NSCLC tumor specimens. Additionally, we demonstrate miR-410 induces stemness through inhibiting Gsk3β but increasing Sox2, Oct4, Nanog and CXCR4, which binds to β-catenin signaling. In conclusion, our findings identify the miR-410/Gsk3β/β-catenin signaling axis is a novel molecular circuit in inducing stemness of NSCLC.